2011
DOI: 10.1063/1.3571596
|View full text |Cite
|
Sign up to set email alerts
|

Small clusters of aluminum and tin: Highly correlated calculations and validation of density functional procedures

Abstract: We present results of molecular electronic structure treatments of multireference configuration interaction (MRCI) type for clusters Al(n) and Sn(n) in the range up to n = 4, and of coupled cluster singles and doubles with perturbative triples corrections (CCSD(T)) type in the range up to n = 10. Basis sets of quadruple zeta size are employed, computed energy differences, such as cohesive energies, E(coh), or dissociation energies for the removal of a single atom, D(e), differ from the complete basis set limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 56 publications
4
52
0
Order By: Relevance
“…This quite satisfactory performance of TPSS is in line with a recent validation of DFT functionals for the metal clusters Al n and Sn n for n up to 8. 40 In comparison with MR-CISD, MR-ACPF, and CCSD(T) treatments, it was found that TPSS is slightly more accurate than PBE, which is better than BP86 and in turn much better than the hybrid functional B3LYP.…”
Section: Ru 17mentioning
confidence: 99%
“…This quite satisfactory performance of TPSS is in line with a recent validation of DFT functionals for the metal clusters Al n and Sn n for n up to 8. 40 In comparison with MR-CISD, MR-ACPF, and CCSD(T) treatments, it was found that TPSS is slightly more accurate than PBE, which is better than BP86 and in turn much better than the hybrid functional B3LYP.…”
Section: Ru 17mentioning
confidence: 99%
“…The reliability of the def2-TZVPP basis set ((14s 9p 3d 1f)/[5s 5p 3d 1f]) was tested in an earlier study on Al clusters. 23 One of the main purposes of the present study is to identify a suitable DFT functional for further investigations of large Al clusters. For this, the segment contraction basis set in the DFT calculations is more appropriate than a general contraction one, such as the correlation-consistent (CC) basis set.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
“…The latter two parameters in a previous study were considered to assess the DFT functionals. 23 Two energetic parameters (vIE and vEDE) are also included, making an assessment of the DFT performance more reasonable. The present study examined DFT performance by calculating the four energetic parameters of Al clusters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Present calculations have shown that, the Ti-Ti bond length of Ti2 dimer predicted by Minnesota M06-L functional is in close agreement with the experimental value. [46] The difference in the Ti-Ti bond length between calculated and experimental results is 0.04 Å. The other DFT functionals that are taken for this study are found to underestimate the Ti-Ti bond length.…”
Section: Ti2 Dimermentioning
confidence: 66%
“…Due to these discrepancies, large structural and energetical values for Cr2 dimer have been obtained. In 2.701 [44] 1.943 ± 0.001 [46] 1.770 [50] 1.679 [52] ≤ 3.4 [57] 2.020 ± 0.020 [59] -2.310 [62] -2.155 ± 0.001 [14] 2.219 [67] 2.350 ± 0.080 [69] summary, the lower level basis set is not suitable for the calculation of structural and energetical parameters in this dimer. From the earlier studies, it is clear that even using higher level ab initio calculations also, one could not produce accurate results in this dimer.…”
Section: Cr2 Dimermentioning
confidence: 94%